Effects of emergency/nonemergency cervical cerclage on the vaginal microbiome of pregnant women with cervical incompetence - Xiao, Yunshan; Huang, Shiting; Yu, Weiwei; Ni, Yan; Lu, Danni; Wu, Quanfeng; Leng, Qin; Yang, Ting; Ni, Meilan; Xie, Jingxian; Zhang, Xueqin (Frontiers in Cellular and Infection Microbiology, 2023)
Background Evaluation of the therapeutic effects of cerclage on preterm birth (PTB) caused by cervical incompetence remains challenging. The vaginal microbiome is associated with preterm births. Thus, this study aimed to analyse the vaginal microbiota of patients with cervical incompetence, explore the relationship between the composition of the vaginal microbiota before cervical cerclage and at term delivery, and assess the effect of cervical cerclage on the vaginal microbiota. Methods Patients (n = 30) underwent cerclage performed by the same surgical team. Vaginal swabs were obtained pre-surgery and seven days post-surgery. A gestational age-matched cohort of healthy pregnant women (n = 20) (no particular abnormality during pregnancy, delivery at term) was used as the control group and sampled during a comparable pregnancy. All collected vaginal swabs were analysed by 16S rRNA gene sequencing. Results When comparing the healthy control and cervical cerclage groups, the enriched microorganism in the healthy controls was G. Scardovia, and the enriched microorganism of the cerclage was G. Streptococcus. α diversity was significantly increased in patients who received cerclage with preterm delivery compared with those with full-term delivery, and the enriched microorganism was F. Enterococcus. A comparison before and after nonemergency cerclage suggested that the enriched microorganisms were G. Lactobacillus and F. Lactobacillaceae before surgery. After nonemergency cerclage, the enriched microorganisms were F. Enterobacteriaceae and C. Gammaproteobacteria. Vaginal microbiota diversity significantly increased, and the proportion of women with Lactobacillus spp.-depleted microbiomes increased after emergency cerclage. Significant differences in β diversity were found between the groups. Before the emergency cerclage, the enriched microorganisms were G. Lactobacillus, O. Alteromonadales, and P. Firmicutes. After emergency cerclage, the enriched microorganisms were P. Actinobacteria, C. Actinobacteria, P. Proteobacteria, F. Bifidobacteriaceae, O. Bifidobacteriales, G. Gardnerella, and G. Veillonella. Conclusion Cerclage (particularly emergency cerclage) may alter the vaginal microbiota by increasing microbiota diversity, decreasing vaginal Lactobacillus abundance, and increasing the abundance of pathogenic bacteria that are not conducive to pregnancy maintenance, thereby affecting surgical efficacy. Therefore, the role of the vaginal microbiome should be considered when developing treatment strategies for pregnant women with cervical incompetence. Clinical trial registration https://www.chictr.org.cn, identifier ChiCTR2100046305.